Tajikistan : Fiscal Risks from State-Owned Enterprises - World Bank (Washington, DC, 2014)
This policy note is part of the World Bank's Programmatic Public Expenditure Review (PER) work program for FY2012-2014. The PER consists of a series of fiscal policy notes, which aim at providing the Government of Tajikistan with recommendations to strengthen budgetary processes and analysis. This policy note, the fifth in the series continues the fiscal policy dialogue conducted in the previous notes. It is structured as follows. Chapter 2 reviews the role of state-owned enterprises (SOE) in Tajikistan's economy and identifies key issues. Chapter 3 assesses the fiscal risks posed by SOEs, especially those in the energy sector. Chapter 4 puts forth possible solutions. Chapter 5 summarizes the main conclusions of this note: 1) despite privatizations and attempts at restructuring, Tajikistan still has a large, inefficient, and heavily indebted public sector; 2) the lack of comprehensive information about the sector undermines budget credibility and budget integrity; 3) multiple but uncoordinated functions, responsibilities, and accountability lines limit government ability to form a comprehensive view of the SOE sector, define a consistent strategy, and effect transparency, performance, reporting, and oversight; 4) elaborate QFAs of SOEs and other public institutions create substantial fiscal risks and undermine the hard-earned benefits of fiscal consolidation; 5) liabilities, explicit and implicit, created by SOE operations are large and must be accounted for and properly delineated; 6) solutions proposed to address the major issues are phasing out QFAs, optimizing the size and scope of the SOE sector, and improving SOE management; and 7) SOE reform should be an integral part of the general reform agenda.